Character Education Based on Al-Gazālī's Sprituality: A Solution to Moral Crisis in the Digital Era - Heni Julaika Putri; Eva Dewi; Via Novelia Najmi (Bulletin of Indonesian Islamic Studies, 2025)
The development of digital technology not only has a major effect on human life, including education, but also causes moral crises such as hoaxes, hate speech, and empathy degradation. This study aims to study Imām Al-Gazālī's perspective on spiritual education as an alternative solution to overcome the moral crisis in the modern era. In addition, this study also creates a plan to implement character education based on spirituality. This type of research is qualitative using a literature study approach. This study collects data by conducting an in-depth analysis of Al-Gazālī's writings and related literature. Such as Al-Gazālī's main works, such as Ihya 'Ulumuddin, Ayyuha al-Walad, and Mizan al-'Amal. The study shows that Al-Gazālī's educational ideas that emphasize the strengthening of morals, purification of the soul (tazkiyatun nafs), and spiritual achievement through reason, heart, soul, and spirit are very relevant to addressing the moral crisis that occurs in the modern era. Primarily, values such as honesty, trustworthiness, patience, gratitude, and self-reflection shape students' characters. Spirituality-based character education can be implemented through curriculum, daily routines, teacher examples, family involvement, and wise use of digital media. This study offers the concept of Al-Gazālī's spirituality-based character education as a solution to the moral crisis of the young generation in the digital era and provides practical guidelines for educational institutions, teachers, and families in forming intelligent, moral, and spiritual individuals.